The Black feminist spatial imagination and an intersectional environmental justice - Ducre, Kishi Animashaun (Environmental Sociology, 2018)
Starting with seminal work from Katherine McKittrick and Katherine McKittrick and the late Clyde Woods, this paper compares and contrasts articulations of justice as espoused by Black feminism, ecofeminism, and the movement for environmental justice. The utilization of an intersectional genealogical approach allows for examination of the ways in which these movements might serve as the ideological bases for a Black feminist spatial imagination and an intersectional environmental justice. A Black feminist spatial imagination is an orientation that accounts for the merger of frames around race, gender, and ecology; it serves as a unique departure from conventional Black feminist analysis by its particular attention to the construct of space in Black feminist epistemology. Analysis reveals that manifestos engage similar strategies around boundedness, an identification among a collective identity and the subject of reproductive justice and liberation as wresting control and self-determination of physical bodies. The final task is an outline of essential tenets for a singular notion of justice of a Black feminist spatial imagination which incorporates the spirit of all of three manifestos and expands current environmental justice discourse to include those ‘who know no one knows’ while highlighting Black women’s agency in environmentally degraded environments. © 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: afro-féminisme; amériques; approches et analyses; corps; environnement; féminismes noirs; intersectionnalité; justice environnementale; justice reproductive; projet charge mentale; régions géographiques; thématiques; écoféminisme; états-unis

Radical reproductive justice: Foundation, theory, practice - Ross, Loretta; Roberts, Lynn; Derkas, Erika; Peoples, Whitney; Bridgewater Toure, Pamela (Feminist press, 2017)
Expanding the social justice discourse surrounding "reproductive rights" to include issues of environmental justice, incarceration, poverty, disability, and more, this crucial anthology explores the practical applications for activist thought migrating from the community into the academy. Radical Reproductive Justice assembles two decades’ of work initiated by SisterSong Women of Color Health Collective, creators of the human rights-based “reproductive justice” framework to move beyond polarized pro-choice/pro-life debates. Rooted in Black feminism and built on intersecting identities, this revolutionary framework asserts a woman's right to have children, to not have children, and to parent and provide for the children they have.
Keywords: afro-féminisme; approches et analyses; discipline; droit; droits des femmes*; intersectionnalité; justice reproductive; justice sociale; maternité; militance; santé; science politique et droit; sciences humaines; sociologie; thématiques

Undivided rights: Women of color organizing for reproductive justice - Silliman, Jael; Fried, Marlene Gerber; Ross, Loretta; Gutiérrez, Elena (Haymarket Books, 2016)
Undivided Rights captures the evolving and largely unknown activist history of women of color organizing for reproductive justice—on their own behalf.Undivided Rights presents a textured understanding of the reproductive rights movement by placing the experiences, priorities, and activism of women of color in the foreground. Using historical research, original organizational case studies, and personal interviews, the authors illuminate how women of color have led the fight to control their own bodies and reproductive destinies. Undivided Rights shows how women of color—-starting within their own Latina, African American, Native American, and Asian American communities—have resisted coercion of their reproductive abilities. Projected against the backdrop of the mainstream pro-choice movement and radical right agendas, these dynamic case studies feature the groundbreaking work being done by health and reproductive rights organizations led by women-of-color.The book details how and why these women have defined and implemented expansive reproductive health agendas that reject legalistic remedies and seek instead to address the wider needs of their communities. It stresses the urgency for innovative strategies that push beyond the traditional base and goals of the mainstream pro-choice movement—strategies that are broadly inclusive while being specific, strategies that speak to all women by speaking to each woman. While the authors raise tough questions about inclusion, identity politics, and the future of women’s organizing, they also offer a way out of the limiting focus on "choice."Undivided Rights articulates a holistic vision for reproductive freedom. It refuses to allow our human rights to be divvied up and parceled out into isolated boxes that people are then forced to pick and choose among.
Keywords: afro-féminisme; amériques; approches et analyses; discours dominant; droits des femmes*; histoire et politique; intersectionnalité; inégalités; justice reproductive; militance; régions géographiques; sofia; système colonial; systèmes d'oppressions; thématiques; états-unis

La mobilisation de la notion de choix dans les discours et débats féministes contemporains une analyse de blogues féministes - Szczepanik, Geneviève (Université du Québec à Montréal, 2013)
Cette thèse porte sur la mobilisation de la notion de choix dans les discours et les débats féministes contemporains. De nombreuses auteures (McRobbie, 2008; Baker, 2008; McCarver, 2011) ont noté que les notions de choix et de liberté individuelle sont très répandues dans les discours féministes et sociaux contemporains, un phénomène qu'elles ont appelé la « rhétorique », l'« idéologie » ou la « politique » de choix. Dans ces discours, les femmes sont considérées comme des personnes qui sont devenues libres, en partie grâce au féminisme. Cette thèse se propose d'aller plus loin en analysant empiriquement la mobilisation de la notion de choix dans les discussions et les débats sur les blogues féministes. Elle a pour objectif de répondre à la question de recherche suivante : En quels termes la notion de choix est-elle mobilisée dans les discours et les débats féministes contemporains à la lumière des échanges recensés sur les blogues féministes? La problématique (chapitre 1) s'appuie tout d'abord sur le constat de la prégnance de la notion de choix dans les discours féministes et sociaux contemporains. Elle montre ensuite l'intérêt d'étudier les discussions et les débats sur les blogues féministes, considérés comme des espaces importants de diffusion, de développement et de renouvellement des discours et des pratiques féministes. Sur le plan théorique (chapitre 2), l'étude articule une approche inspirée des théories féministes radicales matérialistes, des théories féministes noires et postcoloniales et de la sociologie des rapports sociaux. Sont également examinés de façon critique certains courants féministes qui mobilisent particulièrement la notion de choix (notamment la « troisième vague » du féminisme, le « girl power » et le postféminisme). D'un point de vue méthodologique (chapitre 3), la thèse prend comme matériau d'analyse les discussions et les débats mobilisant la notion de choix sur les blogues féministes. Au total, 2 246 billets (et leurs commentaires), provenant de 33 blogues féministes, sont analysés. Basée sur une approche méthodologique inductive et itérative, l'analyse consiste à repérer des thèmes centraux et des idées récurrentes dans les discussions. Le cœur de la thèse consiste en une analyse empirique de la mobilisation de la notion de choix dans les discussions et les débats sur les blogues féministes. Elle fait tout d'abord (chapitre 4) un portrait des blogues féministes, des blogueuses et des commentatrices, notant aussi la diversité des sujets sur lesquels la notion de choix est mobilisée. La thèse s'intéresse ensuite aux discussions mobilisant la notion de choix. Elle aborde (chapitre 5) l'enjeu de l'accès à l'avortement, sujet le plus fréquemment abordé dans le matériau d'analyse. L'analyse montre que les discussions sont souvent axées sur la liberté de choisir (« pro-choix ») et tendent à faire disparaître les discours mettant de l'avant le droit à l'avortement et à la justice reproductive. L'étude analyse enfin (chapitre 6) deux représentations, celle du « féminisme comme liberté individuelle de choix » et celle du « féminisme comme libération collective des femmes », qui développent chacune des conceptions différentes de l'association entre la notion de choix et le féminisme. La thèse rend compte (chapitre 7) du double constat de la prégnance de la notion de choix sur les blogues féministes et de la dépolitisation des discours féministes centrés sur la liberté individuelle de choix. Ces discours ont en effet tendance à effacer les rapports sociaux des analyses féministes de l'oppression des femmes, au profit d'une conception individualiste de leurs choix et de leurs expériences. La thèse insiste en conclusion sur l'importance de (re)mettre de l'avant le potentiel critique du féminisme en ce qui concerne les rapports sociaux, et par le fait même, de repolitiser les discours féministes.
Keywords: 2000 à aujourd'hui; 2000-2009; IREF; afro-féminisme; approches et analyses; avortement; blogues féministes; corps; cours; discipline; féminisme matérialiste; féminismes noirs; justice reproductive; mouvements féministes; médias sociaux; mémoires/thèses; notion de choix; pol4212; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; sciences humaines; sociologie; thématiques